2024
DOI: 10.3390/polym16071019
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Removal of Acid Red 27 by Adsorption on Four Different Chitosan Morphologies

Hongli Wu,
Jiaying Zhou,
Sai Zhang
et al.

Abstract: To investigate the relationship between structures and adsorption properties, four different morphologies of chitosan, with hydrogel (CSH), aerogel (CSA), powder (CSP), and electrospinning nanofiber (CSEN) characteristics, were employed as adsorbents for the removal of Acid Red 27. The structures and morphologies of the four chitosan adsorbents were characterized with SEM, XRD, ATR-FTIR, and BET methods. The adsorption behaviors and mechanisms of the four chitosan adsorbents were comparatively studied. All ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Two classical isotherm models, Langmuir and Freundlich equations, were used to describe the equilibrium properties of adsorption. The fitting curves and R 2 results indicated that these three equilibrium processes were more suitable to be described by the Langmuir model, suggesting that the adsorption sites on the fiber surfaces were uniformly distributed, and the adsorption process could be considered as monolayer adsorption [ 26 ]. As summarized in Table 2 , PAN-BE-NF had the largest adsorption capacity for free bilirubin uptake, with a maximum adsorption capacity up to 818.9 mg g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two classical isotherm models, Langmuir and Freundlich equations, were used to describe the equilibrium properties of adsorption. The fitting curves and R 2 results indicated that these three equilibrium processes were more suitable to be described by the Langmuir model, suggesting that the adsorption sites on the fiber surfaces were uniformly distributed, and the adsorption process could be considered as monolayer adsorption [ 26 ]. As summarized in Table 2 , PAN-BE-NF had the largest adsorption capacity for free bilirubin uptake, with a maximum adsorption capacity up to 818.9 mg g −1 .…”
Section: Resultsmentioning
confidence: 99%